Prevalence of geriatric syndromes in frail patients and mortality risks - Tkacheva, O. N.; Sharashkina, N. V.; Eruslanova, K. A.; Lysenkov, S. N.; Reshetova, A. A.; Matchekhina, L. V.; Ilyushchenko, A. K.; Runikhina, N. K. (Frontiers in Medicine, 2023)
The prevalence of older people in Russian population increases rapidly. Therefore, the concept of healthy aging is becoming crucial in Russia and all over the world, and thus disability prevention is one aspect of this issue. Aim To assess a possible association between geriatric syndromes, comorbidities, and mortality rate among frail patients who receive home medical care in Moscow. Materials and methods The study included 450 patients with home medical care provided by the State Budgetary Healthcare Institution “Diagnostic Center No. 3 of the Moscow Health Department” from June 2019 to April 2021. Physical health, functional, cognitive, social and emotional statuses were evaluated by comprehensive geriatric assessment (CGA). The mortality rate after 1 year was assessed. Results The all-cause case mortality rate in patients during the observation period was 22.4%. There was no difference in age and comorbidities in survivors and deceased patients, but the latter group had more geriatric syndromes. The association between risks of mortality and anemia and some geriatric syndromes, such as malnutrition and hearing impairment, total dependence (Barthel index less than 60) was observed.